2009
DOI: 10.1007/s11430-009-0170-4
|View full text |Cite
|
Sign up to set email alerts
|

Variations in carbon isotope ratios of C3 plants and distribution of C4 plants along an altitudinal transect on the eastern slope of Mount Gongga

Abstract: Variations in carbon isotopic ratios (δ 13 C) of C 3 plants and distribution of C 4 plants were investigatedalong an altitudinal transect on the eastern slope of Mount Gongga, and the environmental effects on them were discussed. It is shown that plants with C 4 photosynthetic pathway mainly occur at altitudes below 2100 m a.s.l., suggesting that the low summer temperature is responsible for the distributional pattern. In addition, δ 13 C of C 3 plants increases with elevation at the region above 2000 m a.s.l.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
37
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 46 publications
8
37
1
Order By: Relevance
“…3) agrees with the previous findings (Guo and Xie 2006;Körner et al 1988Körner et al , 1991Kogami et al 2001;Li et al 2009;Zhu et al 2010). The rate of d 13 C increase with altitude has differed in different studies.…”
Section: Foliar Dsupporting
confidence: 91%
See 1 more Smart Citation
“…3) agrees with the previous findings (Guo and Xie 2006;Körner et al 1988Körner et al , 1991Kogami et al 2001;Li et al 2009;Zhu et al 2010). The rate of d 13 C increase with altitude has differed in different studies.…”
Section: Foliar Dsupporting
confidence: 91%
“…0.70% km -1 ) obtained from alpine areas of the world by Körner et al (1988). However, it was lower than rates of 1.37% km -1 on the Qinghai-Tibet Plateau recorded by Guo and Xie (2006), 1.3 % km -1 on the eastern slope of Mount Gongga, China (Li et al 2009), and 1.4 % km -1 for three genera (Saxifraga, Potentilla and Carex) in south-central Europe (Zhu et al 2010).…”
Section: Foliar Dmentioning
confidence: 61%
“…As for plants, temperature can affect their carbon isotope fractionation via the change in biochemical reaction speed during the photosynthesis process (such as the activity of enzymes participating in photosynthesis) and the stomatal conductance of leaves. There are some studies showing that carbon isotope values of C 3 plants were negatively correlated to temperature (Körner et al, 1991;Ning et al, 2002;Li et al, 2009), while there are even more studies indicating that positive correlation existed between carbon isotopes and temperature (Li et al, 1999;Wang et al, 2002;Liu et al, 2007;Lin, 2008). Still, some other studies suggested that there were no links between Abstract: Uncertainties would exist in the relationship between δ 13 C values and environmental factors such as temperature, resulting in unreliable reconstruction of paleoclimates.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors other than temperature and precipitation, such as altitude, longitude, and latitude, can affect plant δ 13 C (Körner et al, 1991;Sparks and Ehleringer, 1997;Li et al, 2009;Wang et al, 2010). Here, we neglected the effects of these factors when establishing relationships between HIs and δ 13 C because we think that these effects are unlikely to affect our results significantly.…”
mentioning
confidence: 99%
See 1 more Smart Citation